The use of Frequency domain Electro-magnetometer for the characterization of permafrost and ice layers. - ASHRAF NAVIR, MAHSA (2023)
open Since the industrial revolution human activities caused a record-breaking increase in the Earth’s average temperature due to the extensive use of greenhouse gases. [1] As global temperatures increase; glaciers have undergone a significant retreat in the past few decades.[2] The Ice Memory project aims to preserve ice cores from glaciers worldwide, as a record of Earth's past climate. It involves drilling deep into glaciers, extracting ice cores, and storing them in a dedicated facility in Antarctica. This is to prevent the potential loss of valuable climate archives due to glacier retreat which provides future scientists with valuable information for studying historical climate patterns and understanding the role of human activity in climate change. geophysical investigations are typically required to determine the most suitable drilling positions for ice coring. the most common technique for this purpose is the so-called GPR. (Snow cover of several meters limits the use of ERT and active seismic methods.) While each geophysical technique has certain advantages and limitations, combining them can provide a more detailed picture of changes within rock glaciers. In the present study, electromagnetic prospecting in the frequency domain (FDEM) was performed together with the ground penetration radar (GPR). The former is not a commonly used method for studying glacier environments as FDEM has a lower resolution in the study of glaciers with respect to the GPR. However, as we will see in this study, it is a quick and convenient method to study this type of environment, as it provides a large coverage area in a cost-efficient manner, although with a lower resolution with respect to the GPR. Combining these two techniques provide a more detailed map of the glaciers. comparing the GPR and borehole data with the inverted FDEM datasets (CMD-DUO, GF-Instruments) confirms the effectiveness and applicability of FDEM methodology for investigating glacial bodies in mountainous regions. Since the industrial revolution ...